INFLUENCE OF DEFOCUS POSITION ON LASER CUTTING PROCESS IN SHEET STEEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Some researches about influence of defocus position to carry out laser cutting technological process through melting when producing lamellae for electric motors are presented here. Experimental series at defocus position Δf in the range – 3, 5 mm to + 3, 5 mm with two grade electrical steels M250-35A and M530-50A are described, too. The experiments are performed with a technological laser system TruLaser 1030. Functional dependencies of cutting width from defocus position b = b (Δf) have been shown. Theoretical relationships connected to the change of impact on a unit of area working spot over power density qs of the laser radiation and interaction time tproz (respectively cutting speed v), are examined too